Animal and land resource management practices leading to ecological sustainability of smallholder dairy farms in different agro-ecozones of West Bengal, India - CHAKI, THE LATE E K; PAN, S; SANTRA, A K; CHAURASIA, DURGA; KUMARI, KIRAN; SINGH, NISHMA (The Indian Journal of Animal Sciences, 2015)
A study was conducted on the existing animal and land resource management of small holder dairy farms in 3 agro-ecozones of West Bengal. The study revealed that overall average dairy herd size was 5.47 LU in agroecozone I (sub-humid with red and lateritic soils of Purulia) followed by agro-ecozone II [(2.64 LU), warm perhumid with brown and red hill soils and agro-ecozone of Darjeeling], III [(2.63 LU), hot subhumid to humid with alluvial soils of North 24 Parganas]. Proportions of large and medium sized herds were also considerably higher i.e. 58.9 and 30%, respectively, in agro-ecozone I. This showed greater ecological pressure from dairy animals in agro-ecozone I. It was also further revealed that 78.7% of total stock comprising nondescript cattle and buffaloes in agro-ecozone I while farmers, in agro-ecozone II kept crossbred cattle (83.3%) in their herds. Favourable climatic conditions, long term crossbreeding by dairy cooperatives and availability of green fodder might be the reasons of raising higher concentration of crossbred cattle in this agro-ecozone. In agro-ecozone III owing to hot and humidclimatic condition and higher intensity of crop production, farms maintained both nondescript (33%) and crossbred cattle (67%) of total herd strength in low density depending upon their financial capabilities. These animals weremostly raised on crop residues and byproducts under stall-fed condition thus creating lesser ecological pressures ascompared to those of other 2 zones. It was also further revealed that 100% respondents farms in agro-ecozone Iused pastures and post harvested croplands regularly and 31% used forestlands occasionally or regularly for grazing their stock. Farms in this zone practiced on an average 6.7 h of grazing/day which was much higher than agroecozone II (0.37 h) and agro-ecozone III (1.55 h). The differences in the utilization pattern of different types ofgrazing lands between 2 dairying sectors were not remarkable except that use of forest under unorganized sectorswas much higher than organized sector in agro-ecozone I.